Special Component Plan 1995 96 - Planning Commission (Planning Commission, 1995)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on the east coast, about 162 Kins, south of Madras is the largest of these and consists of 12 scattered aieas interspersed v/ith enclaves of Villupuram Ramasamy district and Cuddalore Vallalar District of Tamil Nadu. Karaikal region is about 150 Kms. south of Pondicherry and it is surrounded by Thanjavur District of Tamil Nadu. Yanam region is located about 840 Kms. north east of Pondicherry near Kakinada in Andhra Pradesh.
Government of Pondicherry Planning and Research Department